Happiness and the Quality of Government - John F. Helliwell; Huang, Haifang; Wang, Shun (KDI School of Public Policy and Management, 2020)
This paper uses happiness data to assess the quality of government. Our happiness data are drawn from the Gallup World Poll, starting in 2005 and extending to 2017 or 2018. In our analysis of the panel of more than 150 countries and generally over 1,500 national-level observations, we show that government delivery quality is significantly correlated with national happiness, but democratic quality is not. We also analyze other quality of government indicators. Confidence in government is correlated with happiness, however forms of democracy and government spending seem not. We further discuss three channels (including peace and conflict, trust, and inequality) whereby quality of government and happiness are linked. We finally summarize what has been learned about how government policies could be formed to improve citizens’ happiness.
Keywords: Happiness; Subjective well-being; Quality of government; Delivery quality; Democratic quality; Confidence in government; Government spending; Peace; Conflict; Trust; Inequality